Local Explanations: Editing a Sense of Place in Walter Scott’s Minstrelsy of the Scottish Border (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2014)
This essay examines Walter Scott’s engagement with concepts of place and regionality in the ballad collection Minstrelsy of the Scottish Border (1802-3), revealing ways in which the editor represented and re-imagined the ballads, their associated sense of place and their physical settings.